Seven puzzles of thought and how to solve them an originalist theory of concepts - Sainsbury, R. M. (Richard Mark); Tye, Michael (Oxford : Oxford University Press, 2012)
Sainsbury and Tye present a new theory, 'originalism', which provides natural, simple solutions to puzzles about thought that have troubled philosophers for centuries. They argue that concepts are to be individuated by their origin, rather than epistemically or semantically.
Includes bibliographical references and index.
Description based on online resource; title from PDF title page (viewed on Mar. 5, 2012).
Keywords: Thought and thinking